2011
DOI: 10.1037/a0022249
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial outcomes of telephone-based counseling for adults with an acquired physical disability: A meta-analysis.

Abstract: The results suggest that telecounseling is an effective treatment modality for adults adjusting to a physical disability; however, further trials are needed to establish the long term psychosocial benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 106 publications
0
52
0
Order By: Relevance
“…Telephone based counseling has also been shown to improve coping skills and community integration. 37 Changes need to be seen on the policy level as well, with more coordination and allocation of resources to those with low social integration. Expansion of the Family and Medical Leave Act could guarantee more long-term assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Telephone based counseling has also been shown to improve coping skills and community integration. 37 Changes need to be seen on the policy level as well, with more coordination and allocation of resources to those with low social integration. Expansion of the Family and Medical Leave Act could guarantee more long-term assistance.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the results of online positive psychological interventions do not compare positively with the results of traditional or telephone-based cognitive behavioural therapy of depression in persons with SCI. 15,16 In the original evaluation of Psyfit, Bolier et al 8 reported significant small to moderate effects in persons in the general population, and these effects were larger. It is unclear why in our study, after encouraging short-term results, the longer-term (3 months post intervention) results were disappointing.…”
Section: Satisfactionmentioning
confidence: 99%
“…E-therapy reduces costs for agencies, which require travel of the social workers to assist their clients, such as older adults, people with physical disabilities, and prison populations (Lovejoy Downloaded by [DePaul University] at 12:58 12 October 2014 Dorstyn, Mathias, & Denson, 2011). Social workers working with these populations or in rural areas would have reduced amounts of time and money spent on travel if e-therapy were utilized.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Peer advocacy, support, and programs to help clinical depression are effective for clients who have physical disabilities. When CBT is provided over the phone, the clients reported significant improvements in their depression (Dorstyn et al, 2011).…”
Section: Implications For Depression Treatmentmentioning
confidence: 99%